2011
DOI: 10.1016/j.heares.2011.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus suppression by low-rate electric stimulation and its electrophysiological mechanisms

Abstract: Tinnitus is a phantom sensation of sound in the absence of external stimulation. However, external stimulation, particularly electric stimulation via a cochlear implant, has been shown to suppress tinnitus. Different from traditional methods of delivering speech sounds or high-rate (>2,000 Hz) stimulation, the present study found a unique unilaterally-deafened cochlear implant subject whose tinnitus was completely suppressed by a low-rate (<100 Hz) stimulus, delivered at a level softer than tinnitus to the api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 40 publications
4
93
0
Order By: Relevance
“…One unilateral CI subject (UL1) with single-sided deafness also participated to contrast the effects of electric masking on acoustic stimulation. This subject had nearly normal thresholds ( 25 dB HL re ANSI-1996 for octave frequencies between 250 and 8000 Hz, except 35 dB HL at 4000 Hz) in the non-implanted left ear and was implanted in the right ear for the treatment of severe unilateral tinnitus and sensorineural hearing loss (Cullington and Zeng, 2010;Zeng et al, 2011). Both Institutional Review Board approval and written informed consent were obtained at University of California, Irvine.…”
Section: A Subjectsmentioning
confidence: 99%
“…One unilateral CI subject (UL1) with single-sided deafness also participated to contrast the effects of electric masking on acoustic stimulation. This subject had nearly normal thresholds ( 25 dB HL re ANSI-1996 for octave frequencies between 250 and 8000 Hz, except 35 dB HL at 4000 Hz) in the non-implanted left ear and was implanted in the right ear for the treatment of severe unilateral tinnitus and sensorineural hearing loss (Cullington and Zeng, 2010;Zeng et al, 2011). Both Institutional Review Board approval and written informed consent were obtained at University of California, Irvine.…”
Section: A Subjectsmentioning
confidence: 99%
“…The presence of tinnitus after implantation may be explained by the finding that tinnitus is suppressed mostly when the implant is stimulating the auditory nerve and often reverts back to its original loudness (or becomes louder) soon after stimulation is turned off (Zeng et al 2011;Vlastarakos et al 2014). Therefore, it is plausible that tinnitus could be still bothersome in CI users at night time if the CI is switched off before going to sleep (Chadha et al 2009), and consequently that they would not experience a reduction in the occurrence of tinnitus-related insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory trials indicated that electrical stimulation of the cochlea could suppress tinnitus in many sufferers (Hazell, Graham, & Rothera, 1985;Kuk et al, 1989), which has been further confirmed in recent investigations (Di Nardo et al, 2007;Zeng et al, 2011).…”
Section: Discussionmentioning
confidence: 76%